MODEL PENGEMBANGAN KEMITRAAN USAHA PERIKANAN TANGKAP DENGAN LEMBAGA KEUANGAN DI KABUPATEN INDRAMAYU - Charles Bohlen Purba; John Haluan; Domu Simbolon; Sugeng H. Wisudo (Buletin PSP, 2008)
Less on developing and contributing fisheries sector on Gross National Product (GNP), especially capture fishing efforts in Indramayu Regency, dominantly because of capital limitation and imprecisely capture fishing sector development. This research is trying to analyze financial feasibility of capture fishing sector and its relationship with financial institutions. The analyzing methods would be referred to Hanley and Spash (1993) there are Net Present Value (NPV), Net Benefit – Cost Ratio (B/C Ratio), Internal Rate of Return (IRR), Return of Investment (ROI), and Payback Period (PP). The results shows that capture fishing with payang, drift gill net (JIH) and state gill net (JIT) are capture fisheries efforts with good financial conditions (NPV Payang = Rp 169.798.012, NPV JIH = Rp 344.738.291, NPV JIT = Rp 454.465.535, and the other five capture fisheries efforts have NPV, B/C Ratio, IRR, ROI and PP appropriate with terms and conditions, then its could be more development and proper to get financial institutions support. Capture fisheries with fishhook and fishing line are not properly to be develop. There are four potential financial institutions which could support the capture fisheries efforts, but for now, only Jabar-Banten Bank and KPL Mina Sumitra which needed its actions. And the kind of credits/payments/ services which could be optimally used from Jabar-Banten Bank are Micro Credits and Peduli Credits, with each reaching Rp 422.400.000 and Rp 105.600.000 each year. KPL Mina Sumitra consist of Investment Credits, Micro Credits and Development Services are reaching Rp 9.280.000.000, Rp 928.000.000 and Rp 464.000.000 each year. There are financial institution which not needed its services because of the credits scale which offered are not suitable, the relations not connected, there are problems in collateral, and trust factor.